2016
DOI: 10.1038/srep21713
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of E-cadherin expression promotes migration ability of esophageal cancer cells

Abstract: Losing the E-cadherin plays an important role in the metastasis of cancer. The regulation of the expression of E-cadherin is unclear. Circadian rhythm alteration is associated with the pathogenesis of a number of cancers. This study aims to investigate the role of one of the circadian proteins, period-2 (Per2) in repressing the expression of E-cadherin in esophageal cancer (esophageal cancer). We observed that the levels of circadian protein Per2 were significantly increased and E-cadherin was significantly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…One of the hallmarks of EMT is the functional loss of E‐cadherin, which is associated with epithelial‐to‐mesenchymal transition in cancer . A previous study demonstrated that reduced E‐cadherin decreases the strength of cellular adhesion, resulting in increased cellular motility; however, the overexpression of E‐cadherin was sufficient to prevent migration. Therefore, E‐cadherin plays a critical role in migratory ability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the hallmarks of EMT is the functional loss of E‐cadherin, which is associated with epithelial‐to‐mesenchymal transition in cancer . A previous study demonstrated that reduced E‐cadherin decreases the strength of cellular adhesion, resulting in increased cellular motility; however, the overexpression of E‐cadherin was sufficient to prevent migration. Therefore, E‐cadherin plays a critical role in migratory ability.…”
Section: Discussionmentioning
confidence: 98%
“…To investigate the mechanism by which oridonin increased the expression of E‐cadherin in this study, the transcription factors snail and slug were investigated as these two proteins bind to the E‐cadherin promoter to suppress E‐cadherin expression . The results showed that the expression of snail and slug was significantly decreased by oridonin when compared with their expression in the control group . Furthermore, the expression of vimentin was significantly decreased after the application of oridonin.…”
Section: Discussionmentioning
confidence: 99%
“…Insert A is generally linked to localization of NLGN1 at inhibitory synapses, whereas insert B localizes NLGN1 at excitatory synapses (Chih, Gollan, & Scheiffele, ). Additionally to an increase in its mRNA level in Clock knock‐down cell culture, E‐cadherin expression is decreased by Per2 overexpression in esophageal cancer cells (Li et al., , ). This overexpression of Per2 increases the level of histone deacetylase HDAC1 at E‐cadherin promoter, which then increases the recruitment of repressors (Li et al., ).…”
Section: Adhesion and Scaffolding Moleculesmentioning
confidence: 99%
“…It is mentioned as a typical tumor suppressor gene and plays a critical role in carcinogenesis. Loss expression of CDH1 enables disaggregation of cancer cells from one another and increases their metastatic potential [11,12]. However, the pattern of CDH1 expression and its clinical implication remain to be elucidated in AML.…”
Section: Introductionmentioning
confidence: 97%